From Early Immunomodulatory Triggers to Immunosuppressive Outcome: Therapeutic Implications of the Complex Interplay Between the Wavebands of Sunlight and the Skin - Vieyra-Garcia, Pablo A.; Wolf, Peter (Frontiers in Medicine, 2018)
Phototherapy is an efficient treatment for many cutaneous diseases that involve the activation of inflammatory pathways or overgrowth of cells with aberrant phenotype. In this review, we discuss the recent advances of photoimmunology, focusing on the effects of UV-based therapies currently used in dermatology. We describe the molecular responses to the main forms of photo(chemo)therapy such as UVB, UVA-1 and PUVA. They include the triggering of apoptotic or immunosuppressive pathways that help to clear diseased skin. The early molecular response to UV involves DNA photoproducts, the isomerization of urocanic acid, the secretion of biophospholipids like platelet activating factor, and the activation of aryl hydrocarbon receptor and inflammasome, as well as vitamin D synthesis. These events occur simultaneously in a complex interaction, together they regulate the activity of the immune system both locally and systemically resulting in apoptosis of neoplastic and/or benign cells, reduction of cellular infiltrate, and regulation of cytokines and chemokines. Regulatory T-cells and Langerhans cells among other cellular populations that reside in the skin are deeply affected by UV exposure and therefore are important players in the mechanisms of immunomodulation and the therapeutic value of UV treatment. We weight the contribution of these cells to the therapeutic application of UV and how they may participate in transferring the direct impact of UV on the skin into local and systemic immunomodulation. Moreover, we review the therapeutic mechanisms revealed by investigations with patients and animal models in the most common cutaneous diseases treated with phototherapy such as psoriasis, atopic dermatitis, vitiligo and cutaneous T cell lymphoma. The better understanding of phototherapeutic mechanisms in those diseases will help to advance treatment in overall and make future therapeutic strategies more precise, targeted, personalized, safer and more efficient.